Integrating Next-Generation Sequencing in the Clinical Pharmacogenomics Workflow - Giannopoulou, Efstathia; Katsila, Theodora; Mitropoulou, Christina; Tsermpini, Evangelia-Eirini; Patrinos, George P. (Frontiers in Pharmacology, 2019)
NA